2020
DOI: 10.1002/acn3.51026
|View full text |Cite
|
Sign up to set email alerts
|

Idebenone increases chance of stabilization/recovery of visual acuity in OPA1‐dominant optic atrophy

Abstract: We previously documented that idebenone treatment in OPA1-Dominant Optic Atrophy (OPA1-DOA) led to some degrees of visual improvement in seven patients. We here present the results of a cohort study, which investigated the effect of off-label idebenone administration in a larger OPA1-DOA group compared with untreated patients. Inclusion criteria were: OPA1-DOA clinical and molecular diagnosis, baseline visual acuity (VA) greater than/equal to counting fingers and treatment duration greater than 7 months. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…Nevertheless, patients’ results are more encouraging: a pilot study on seven DOA patients documented encouraging results after 1-year of idebenone administration, with some improvement of visual function [ 246 ]. A recent retrospective cohort study investigated the effect of off-label idebenone administration on visual outcome in a DOA group of 87 patients, demonstrating that the treatment was significantly associated with stabilization/recovery of visual acuity [ 247 ].…”
Section: “One-size-fits-all” Approachesmentioning
confidence: 99%
“…Nevertheless, patients’ results are more encouraging: a pilot study on seven DOA patients documented encouraging results after 1-year of idebenone administration, with some improvement of visual function [ 246 ]. A recent retrospective cohort study investigated the effect of off-label idebenone administration on visual outcome in a DOA group of 87 patients, demonstrating that the treatment was significantly associated with stabilization/recovery of visual acuity [ 247 ].…”
Section: “One-size-fits-all” Approachesmentioning
confidence: 99%
“…Table 1 summarizes all the therapeutic approaches used up to date. [197] OPA1 coenzyme Q10 No evidence for a significant benefit in dominant optic atrophy (DOA) patients [198] idebenone In 74 of 87 DOA treated patients, an increased visual acuity was observed after at least 7 months of administration [199] tolfenamic acid…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Unfortunately, there is currently no established treatment for OPA1-linked diseases. It has been reported that idebenone treatment induces some degrees of visual improvement in OPA1 -DOA patients ( 23 , 24 ), whereas it presents a limited therapeutic effect in a mouse model of OPA1-related DOA, strictly correlated to NQO1 expression ( 25 ). Even if there is an ongoing effort to genetically correct OPA1 mutations ( 26 ), gene therapy is still far from clinical use ( 12 ).…”
Section: Introductionmentioning
confidence: 99%